The usefulness of online auction to UiTM Shah Alam community / Noriswandi Asmuni - Asmuni, Noriswandi (2005)
The exponential growth of the Internet has led to a radical change in the way business is conducted. A few years ago, the application of auction on Internet (or online auction) was not yet fully explored by the organizations to distribute or sell their products, new and old. But today, all things have changed. Online auctions are become increasing important buying and selling channels for organizations and individuals (Turban et al., 2004) This research projects looks into the role • online auction plays in a society. The scope of the research is on UiTM Shah Alam community. Question/ were distributed to about 200y(among the UiTM Shah Alam community of staff and students. From the findings, the perceived usefulness of online auction was determined for this community.